2012
DOI: 10.1111/j.1601-0825.2012.01948.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of systemically administrated zoledronic acid on the osseointegration of dental implants

Abstract: A single dose of systemic ZA administration increases the rate of NBF and augments the quality of the bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 43 publications
2
28
0
1
Order By: Relevance
“…The influence of the use of bisphosphonates in implant dentistry has been studied extensively, both their systemic use [27][28][29] and local use by means of direct application to the surgical alveolus 13,22,23,25 or by immobilization of the medication on the implant surface. 7,15,16,[19][20][21] In this study, local application of bisphosphonate was used in order to benefit from its biomodulating influence on osseointegration in the absence of the possible systemic effects of this drug.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the use of bisphosphonates in implant dentistry has been studied extensively, both their systemic use [27][28][29] and local use by means of direct application to the surgical alveolus 13,22,23,25 or by immobilization of the medication on the implant surface. 7,15,16,[19][20][21] In this study, local application of bisphosphonate was used in order to benefit from its biomodulating influence on osseointegration in the absence of the possible systemic effects of this drug.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have demonstrated that moderately rough surface implants, prepared using the same methods used to manu- following ibandronate administration in rabbit femur 40 or ZA administration in rabbit tibia, 41,42 while others have failed to produce statistically significant differences following alendronate administration in rabbit femur. 43 Furthermore, the extrapolation of animal data on osseointegration in long bone to the clinical situation within the oral cavity has to be interpreted with caution.…”
Section: Discussionmentioning
confidence: 58%
“…A limited number of studies to date have demonstrated the influence of BPs, and ZA in particular, on osseointegration in non‐estrogen deficient animals such as those used in the present study. Several pre‐clinical animal trials have used histomorphometric analysis to show an improvement in osseointegration, following ibandronate administration in rabbit femur or ZA administration in rabbit tibia, while others have failed to produce statistically significant differences following alendronate administration in rabbit femur . Recently, de Olivier and co‐workers (2014) demonstrated no statistical differences in the values of BIC (%) for the entire observational periods after the surgical placement of titanium implants in rat tibiae between the ZA and control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Review of the current literature reflects a limited, but growing, knowledge of the relative risks to dental implant treatment in patients receiving bisphosphonate medication [139,[170][171][172][173][174][175][176][177][178][179]. There have been several case reports and series that have evaluated implant failures in patients receiving intravenous bisphosphonate therapy [180], while other retrospective studies have indicated that there may be risks of osteopathology developing in patients receiving oral bisphosphonates and dental implant treatment [10][11][12][13][14].…”
Section: Bisphosphonates and Dental Implantsmentioning
confidence: 99%